A Case Study of Prospective Teachers Engaged in Professional Noticing of their Students' Mathematical Thinking - Sarah Selmer; Denise Lindstrom; Erna Lampen (MDPI AG, 2022)
In this study, prospective teachers engaged in professional noticing of their students' mathematical thinking captured in pieces of written work. Researchers then worked to characterize the prospective teachers' professional noticing using a lens of responsive teaching. Results indicate that prospective teacher decisions about how to respond to their students' mathematical thinking fall on a responsiveness continuum, often shifting in responsiveness across pieces of student written work. The findings of this study provide guidance for teacher educators who work to develop K-12 educators' responsive teaching practices.